Controlling Dengue: Effectiveness of Biological Control and Vaccine in Reducing the Prevalence of Dengue Infection in Endemic Areas - Paul, Bryan; Tham, W. (Scientific Research Publishing, 2016)
With the increased prevalence of dengue infection in tropical countries, concerned members of the public are now pressing their local health ministries to act immediately and effectively in managing the rising numbers of reported cases. This includes reviews of the methodologies and the effectiveness of current combative systems to find other possible novel approaches that might yield better results. One of those novel approaches is the integration of a parasite into mosquito vector, manipulating the parasite-host interaction to reduce the transmission of dengue in endemic hotspots. Another alternative is by Sanofi-Pasteur’s dengue vaccine that showed over 60.8% success rate in reducing severe dengue infection in children aged 9 - 16 during its final clinical implementation phase. This report will compare and contrast these two novel ideas to determine which of the approaches are more likely to be effective in the long run. The aspects covered will include the application, effectiveness, functionality, and problems with these approaches. The results could then be utilised by governments or organizations to select precise and effective methods in reducing the prevalence of dengue infections in their countries.